The phenomenon of globalisation as the greatest modern megatrend - Jarantowska, Marta (Kultura-Społeczeństwo-Edukacja, 2019)
The purpose of the article is to present the complexity of the notion of globalisation and the many definitions of this phenomenon. The article presents positions of various authors, including a rich set of variables that determine them. It highlights the importance of blurring boundaries, permeation of cultures, closer relations and multiplicity of interactions on a micro and macro scale. It emphasizes the topic of values and self-awareness of modern human beings in the context of the numerous possibilities and options of choice, as well as its relation to diversity and “Otherness”. It attempts to define the aspirations of contemporary human beings by analysing the dichotomy of autonomy and dependence. Globalisation is described as a phenomenon widely developed and still progressing, carrying both opportunities and risks.